PENYULUHAN SERTIFIKASI HALAL DALAM MENINGKATKAN PRODUKTIFITAS RUMAH POTONG HEWAN - Evi Adriani; Yunan Surono; Dwi Putri Budiningtyas; Azizah Azizah (Pengabdian Deli Sumatera, 2024)
ABSTRACT This research analyzes halal certification at slaughterhouses in Auduri Penyegat Bawah with a focus on product processes and management systems that ensure product halal. The research method used is a descriptive approach with a qualitative research type. The research results show that the slaughterhouse does not yet have halal certification, but has met animal health requirements. Evaluation involves halal commitment and management, facilities, tools, halal product processes, monitoring and evaluation. Even though the facilities are adequate and the products are proven to be healthy, halal certification is still needed to maintain consumer trust and open up better business opportunities. Recommendations include the development of training programs for employees and a halal testing process to obtain certification. Keywords: Halal Certification, Productivity